Attenuated Actinobacillus pleuropneumoniae double-deletion mutant S-8∆clpP/apxIIC confers protection against homologous or heterologous strain challenge. Issue 1 (December 2016) - Xie, Fang; Li, Gang; Zhou, Long; Zhang, Yanhe; Cui, Ning; Liu, Siguo; Wang, Chunlai
Abstract Background Actinobacillus pleuropneumoniae is the etiological agent of porcine pleuropneumonia, which leads to large economic losses to the swine industry worldwide. In this study, S-8△clpP△apxIIC, a double-deletion mutant ofA. pleuropneumoniae was constructed, and its safety and protective efficacy were evaluated in pigs. Results The S-8△clpP△apxIIC mutant exhibited attenuated virulence in a murine (BALB/c) model, and caused no detrimental effects on pigs even at a dose of up to 1.0 × 109 CFU. Furthermore, the S-8△clpP△apxIIC mutant was able to induce a strong immune response in pigs, which included high levels of IgG1 and IgG2, stimulated gamma interferon (IFN-γ), interleukin 12 (IL-12), and interleukin 4 (IL-4) production, and conferred effective protection against the lethal challenge withA. pleuropneumoniae serovars 7 or 5a. The pigs in the S-8△clpP△apxIIC immunized groups have no lesions and reduced bacterial loads in the lung tissue after challenge. Conclusions The data obtained in this study suggest that the S-8△clpP△apxIIC mutant can serve as a highly immunogenic and potential live attenuated vaccine candidate againstA. pleuropneumoniae infection.